PENDEKATAN SEJARAH DALAM PENGKAJIAN ISLAM - Abdur Rahman (Program Studi Sejarah Peradaban Islam Institut Agama Islam Darullughah Wadda'wah, 2022)
This article is titled “Historical Approach in Islamic Studies”. Study of Islam is a scientific discipline which as old as the age of Islam appearance itself. This research has purpose to study about the connection between religion and history of human. The basic knowledge from this research is explanation the important role of historical approach in Islamic studies. Analysing long history of Muslim periodization in building civilizations with different characteristics, but still uphold Islamic brotherhood sourced from al-Quran and al-Hadits. This article is scientific writings based on library research by collecting every form of history informations which are relevant to the topic and sub-containts in the object of research’s scope. The result of this research shows historical approach in Islamic studies can be known by two things: Islam normative (doctrinaire) and Islam history (scientific). Doctrinaire approach is seeing Islam as religion doctrine that has to be done ideally. Then, scientific approach is seeing Islam as a knowledge.